2016
DOI: 10.1038/nmat4708
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical stiffness in lithium-ion batteries

Abstract: Although lithium-ion batteries are ubiquitous in portable electronics, increased charge rate and discharge power are required for more demanding applications such as electric vehicles. The high-rate exchange of lithium ions required for more power and faster charging generates significant stresses and strains in the electrodes that ultimately lead to performance degradation. To date, electrochemically induced stresses and strains in battery electrodes have been studied only individually. Here, a new technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 49 publications
6
97
0
Order By: Relevance
“…Consecutive accumulation of strain and stress on other battery components is induced, which apparently has a negative impact on maintaining the microstructure integrity of silicon particles as well as the reversibility of the structural changes of thesilicon electrode in the long term. [24] During subsequent delithiation, which is shown in the second row in Figure 2b,t he fragmented granules tend to recover back to the previous particles hape. The cracks between the granules disappear stepwise with lithium being extracted from Li x Si accompanied by ad ecrease in transmission.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Consecutive accumulation of strain and stress on other battery components is induced, which apparently has a negative impact on maintaining the microstructure integrity of silicon particles as well as the reversibility of the structural changes of thesilicon electrode in the long term. [24] During subsequent delithiation, which is shown in the second row in Figure 2b,t he fragmented granules tend to recover back to the previous particles hape. The cracks between the granules disappear stepwise with lithium being extracted from Li x Si accompanied by ad ecrease in transmission.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, fracture of particles significantly contributes to the volume expansion of the electrode not only laterally within the electrode plane but also in the longitudinal direction (i.e., perpendicular to the plane shown in Figure b). Consecutive accumulation of strain and stress on other battery components is induced, which apparently has a negative impact on maintaining the microstructure integrity of silicon particles as well as the reversibility of the structural changes of the silicon electrode in the long term …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] However, the energy density of the LIBs is mainly controlled by the electrode materials, especially the cathode materials. [6] Among a large number of cathode candidates, LiCoO 2 has been widely used as a commercialized cathode material for LIBs due to its good cycling properties and excellent rate capability.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Foralloying and conversion reactions, the volume expansion is more severe than that occurs during an intercalation reaction, [2] and previous reports have shown that excessive volumetric changes result in pulverization of the initial electrode materials,disconnection of active materials from the binder and current collector,and damage of the established solid-electrolyte interface layer. [1] Foralloying and conversion reactions, the volume expansion is more severe than that occurs during an intercalation reaction, [2] and previous reports have shown that excessive volumetric changes result in pulverization of the initial electrode materials,disconnection of active materials from the binder and current collector,and damage of the established solid-electrolyte interface layer.…”
mentioning
confidence: 99%